Biofuels as alternative energy sources for shipping industry : assessment of straight vegetable oil as marine fuel - Low, Chun Feng (2019)
Increase in environmental awareness has stressed the industry to move towards a greener and environmentally-friendlier industry. International Maritime Organisation (IMO) has introduced “Initial IMO Strategy” in view of the Paris Agreement1 laid out by the United Nation. The purpose of this strategy is to reduce GHG emission in the shipping industry. Though guidelines have yet rolled out by IMO, steps are taken to review on the emission from shipping activities. To tackle this issue from a long-term perspective, biofuels are considered due to its biogenic characteristics. In light to facilitate the introduction of IMO Strategy, biofuels will be assessed in this paper. This paper aims to analyse the outlook of biofuel to be integrated into maritime industry for the next 10-15 years in line with the IMO Strategy. First, various biofuel, such as biodiesel, straight vegetable oil, biomethanol and biomethane, will be studied and assess on their potentiality. Current conventional marine fuel and energy consumption from shipping activities will be examined. This is followed by the selection of biofuel will be based on its prospective to be integrated into the industry, in which this paper will focus on straight vegetable oil (SVO). An extensive literature review on straight vegetable oil is carried out. To fill in the gaps from literature review, questionnaires will be sent to various industry players. Feedbacks from the industrial stakeholders enabled the understanding of the level of importance of different criteria considered in fuel selection. Finally, evaluation of SVO would be in terms of economic, technical, environmental and social performance from in-depth literature review, together with the results from questionnaire. Afterwards, SWOT analysis is conducted on SVO into shipping activities before arriving to conclusion and recommendation. This paper concluded that SVO could possibly be a transitional fuel for the shipping industry with the implementation of IMO Strategy, before the next generation of fuel such as algae oil to achieve commercial stage.